Utilization Digital Health: Opportunities and Challenges in Enhancing Tuberculosis Treatment - Sri Hartini Ma; Achmad Solechan; Asti Nuraeni; Dayat Trihadi; Nafisatun Nisa (International Journal of Health and Medicine, 2024)
Digital health interventions hold promise for patient-centered care, as they enable remote monitoring of patients and can be used to easily remind patients to take their medications. This study used a literature review technique with research collecting 30 research publications related to the use, opportunities and challenges of digital health in the treatment of tuberculosis. The literature review technique aims to evaluate and analyze previous research to provide context, show gaps in research, and support arguments for the research to be conducted. Several conclusions from this literature review research include: (1) Digital health has a significant role as an intervention in the management of tuberculosis patients. (2) Digital health offers great opportunities to improve the management and treatment of tuberculosis patients. The opportunity for digital health as an intervention for tuberculosis patients is very promising and can have a significant impact on various aspects of managing this disease. (3) Although digital health offers many opportunities for managing tuberculosis, there are also various challenges that must be faced in its implementation, including: challenges of technology access, patient compliance and engagement, data security and privacy, integration with traditional health systems, costs and funding, quality content and information as well as cultural and language barriers.